2005
DOI: 10.1111/j.1442-2042.2004.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of early primary realignment in children with posterior urethral injury

Abstract: Aim: The aim of this retrospective study was to compare the results of delayed repair and early primary realignments in patients with posterior urethral injury. Methods : From 1990: From to 2003 children were admitted to the Medical Faculty of Uluday University, Bursa, Turkey, for posterior urethral injuries. Traffic accidents were the most common cause of injury (n = 17). Twelve patients (60%) who were referred early (1-10 days) underwent early realignment over a urethral tube. A total of eight patients (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Patients undergoing PR of PFUI may have less severe urethral strictures when compared to patients undergoing SP diversion alone. 23,24 …”
Section: Guideline Statementsmentioning
confidence: 99%
“…Patients undergoing PR of PFUI may have less severe urethral strictures when compared to patients undergoing SP diversion alone. 23,24 …”
Section: Guideline Statementsmentioning
confidence: 99%
“…1,4,[9][10][11][12][13] Concerning the timing of the operation, there is increasing evidence in the literature that immediate realignment of lacerated urethra is possible (provided that the patient is stable and the surgeon experienced) and has lower rate of postoperative strictures compared with delayed end-to-end anastomosis while the rate of incontinence and ED stays the same. [14][15][16] Despite this possible advantage of early realignment, we believe that delayed urethral anastomosis is safer for the severely injured patient and gives more time to the surgeon to plan not only the operation itself but also preoperative imaging. Well-planned imaging may also include pelvic MRI that is available in all pediatric centers today when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, many surgeons have prohibited immediate surgical management in children, thinking that any attempt to evacuate the pelvic hematoma may trigger more bleeding and result in greater injury to the pelvic nerves and vessels. Balkan et al [4] compared the results of repair of posterior urethral injury in children managed by delayed repair versus early realignment, and they concluded that urethral stricture in patients who underwent early realignment was less developed than in those who underwent delayed repair. Nerh et al [5] reported their long-term follow up of 22 children and documented that immediate urethral realignment in children should be attempted to prevent long-term complications.…”
Section: Discussionmentioning
confidence: 99%